Effects of glycosaminoglycan content in extracellular matrix of donor cartilage on the functional properties of osteochondral allografts evaluated by micro-CT non-destructive analysis. - Yong Jun Jin; Do Young Park; Sujin Noh; HyeonJae Kwon; Dong Il Shin; Jin Ho Park; Byoung-Hyun Min (PLoS ONE, 2023)
Osteochondral allograft (OCA) is an important surgical procedure used to repair extensive articular cartilage damage. It is known that chondrocyte viability is crucial for maintaining the biochemical and biomechanical properties of OCA, which is directly related to the clinical success of the operation and is the only standard for preoperative evaluation of OCA. However, there is a lack of systematic research on the effect of the content of cellular matrix in OCA cartilage tissue on the efficacy of transplantation. Therefore, we evaluated the effect of different GAG contents on the success of OCA transplantation in a rabbit animal model. Each rabbit OCA was treated with chondroitinase to regulate glycosaminoglycan (GAG) content in the tissue. Due to the different action times of chondroitinase, they were divided into 4 experimental groups (including control group, 2h, 4h, and 8h groups). The treated OCAs of each group were used for transplantation. In this study, transplant surgery effects were assessed using micro-computed tomography (μCT) and histological analysis. Our results showed that tissue integration at the graft site was poorer in the 4h and 8h groups compared to the control group at 4 and 12 weeks in vivo, as were the compressive modulus, GAG content, and cell density reduced. In conclusion, we evaluated the biochemical composition of OCAs before and after surgery using μCT analysis and demonstrated that the GAG content of the graft decreased, it also decreased during implantation; this resulted in decreased chondrocyte viability after transplantation and ultimately affected the functional success of OCAs.